2020
DOI: 10.1029/2020gl090401
|View full text |Cite
|
Sign up to set email alerts
|

Paleofire, Vegetation, and Climate Reconstructions of the Middle to Late Holocene From Lacustrine Sediments of the Toushe Basin, Taiwan

Abstract: We identified four climatic stages between 6.2 and 1.3 cal kyr before present (BP) based on pollen and charcoal concentrations by high-resolution Accelerated mass spectrometer (AMS) 14 C-dated sediment profile from Taiwan's Toushe Basin. From 6.2 to 4.6 cal kyr BP, the region was warm-wet with infrequent wildfires and dominant subtropical evergreen broad-leaved forests. The climate was cooler-drier from 4.6 to 3.0 cal kyr BP, with a decline in forest and increased fire frequency. From 3.0 to 2.1 cal kyr BP, cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 88 publications
(116 reference statements)
2
10
0
Order By: Relevance
“…It is also in line with climate inference from a compilation of peat initiation records in Fujian (Lei et al, 2017). Moreover, a shift to drier conditions during the mid-to-late Holocene transition has also been suggested by paleoclimate records in Toushe Basin and Retreat Lake from Taiwan, Southeast China (Selvaraj et al, 2007;Z. Huang et al, 2020; Figure 2).…”
Section: Hydrological Reconstructionsupporting
confidence: 87%
See 3 more Smart Citations
“…It is also in line with climate inference from a compilation of peat initiation records in Fujian (Lei et al, 2017). Moreover, a shift to drier conditions during the mid-to-late Holocene transition has also been suggested by paleoclimate records in Toushe Basin and Retreat Lake from Taiwan, Southeast China (Selvaraj et al, 2007;Z. Huang et al, 2020; Figure 2).…”
Section: Hydrological Reconstructionsupporting
confidence: 87%
“…et al, 2013); 2: Hongyuan peatland (Seki et al, 2011); 3: Shennong Cave (Zhang, Cheng, et al, 2018); 4: Dongge Cave (Dykoski et al, 2005); 5: Toushe Basin (Z. Huang et al, 2020), and 6: Shuizhuyang peat deposit (this study).…”
Section: Methodsmentioning
confidence: 50%
See 2 more Smart Citations
“…(2015) [87] found that during the La Niña years, southern Taiwan experienced decreased rainfall in April-June and increased rainfall in July-September, which were associated with weaker meiyu rainfall and stronger typhoons, respectively. For central Taiwan, [88] discovered that frequent drought-related wildfires, which impact vegetation in central Taiwan, were associated with the dry and cool weather during the El Niño years. Figure 8 displays the largest change in direction of the NDVI and temperature datasets, which should be interpreted carefully, considering that the largest change in direction was a snapshot of the study period and, thus, could not reveal the whole trajectory of the time series.…”
Section: Enso Eventsmentioning
confidence: 99%